Income Taxation and Labor Supply: A Narrative Review of International Findings with Focus on High-Income Economies - Yolifiandri; Lestari, Putri Ayu; Nasrulloh, Ubaid Fandi (Sinergi International Journal of Economics, 2024)
This narrative review investigates the impact of income taxation on labor supply across diverse demographic and economic contexts. The study aims to synthesize empirical findings and theoretical insights regarding how tax policy structures influence labor participation. A narrative review methodology was employed, drawing on peer-reviewed literature sourced from Scopus and Google Scholar, guided by targeted keyword strategies and strict inclusion criteria. The review examined studies on tax progressivity, informality, gender disparities, and institutional influences affecting labor supply. Key findings indicate that income taxation exerts complex and varied effects on labor supply. Gendered responses to tax structures, especially under joint taxation regimes, tend to suppress female participation, while separate filing systems improve equity and engagement. Informal labor markets expand when tax compliance is burdensome or perceived as unfair, particularly in developing economies with weak institutional trust. Meanwhile, higher marginal tax rates diminish labor effort among high-income earners, underscoring the importance of balanced progressivity. The review concludes that effective tax policy requires behavioral, institutional, and demographic sensitivity. Tailored reforms can enhance labor market participation and revenue generation without compromising equity. Future research should focus on underexplored regions and emerging labor sectors to guide adaptive, inclusive tax system design for sustainable development.